Caracterização de aplicativos móveis de emagrecimento - GOMES, Brendon Roberth Guimarães (2023)
Given the largescale creation of nutritionoriented applications and the dissemination of information to persuade the population to use these tools, this review aimed to characterize the functionalities of mobile nutrition applications aimed at weight loss. For this, 50 mobile health and fitness apps were downloaded from the Google Play Store for the Android smartphones of one of the authors. Following the use of the 50 applications, ten mobile applications were selected based on eligibility criteria related to nutritional assistance. The features were checked and compared as present and absent, and broken down for paid functions, were also characterized and described according to their operation in the applications. Depending on the results, only Fast Secret and Calorie Counter Easyfit are free and the maximum price of the paid functions corresponds to three consultations with a nutritionist. The main functionalities that assist the nutritionist are: Body Mass Index, reminders and alerts for water and food consumption, insertion of anthropometric measurements, calculation of caloric expenditure in physical activities and energy needs, record of food consumption, analysis of macronutrients, calorie counters and online technical support, which needs a standardization in order to promote ethical character. The usability of the applications although important, however, does not interfere in the characterization of the functionalities to assist the nutritionist. The combination of functions adds credibility and proficiency to the nutritionist's assistance in working with applications. The study offers character of accomplishment of an ideal application, following the professional ethics and nutrition supervision, as well as alert on the possibility of creating laws and norms for this new scenario of applications and nutritionist. O Yazio Calorie Counter is the best application classified in the comparability of functionalities, it is the indicated to assist the nutritionist in the performance and relationship with the patientuser to promote practicality of care.